2014
DOI: 10.1177/2151458514520701
|View full text |Cite
|
Sign up to set email alerts
|

Open Reconstruction of Complex Proximal Metadiaphyseal Fragility Fractures of the Humerus

Abstract: Purpose: A proactive surgical and rehabilitation protocol was implemented to manage humeral fractures involving both the proximal end and shaft in an older patient population. Primary treatment goals were early return to function and reliable fracture union with minimal complications. Methods: From 2008 to 2012, 21 such operations were performed; 18 were considered ''fragility'' fractures based on mechanism, patient age, and evidence of osteopenia or osteoporosis. Open reduction and internal fixation (ORIF) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…14,15 Whereas we preferred the use of the dual plating for the case, which can increase the fracture stabilization similar to the other 2-column fracture types like tibial plateau, distal humerus and plafond fractures. 16,17 In our case, surgery was done by 1 incision lateral to femur. Fibrotic areas and bone sequesters were debrided completely, obtained cancellous bone graft from iliac crest placed in the fracture site, direct reduction done followed by temporary fixation with K-wires, and longlocked lateral distal femoral plate used for the lateral column, then, under direct vision with neurovascular protection, a relatively small reconstructive plate was used at anteromedial distal femur for the medial column.…”
Section: Discussionmentioning
confidence: 92%
“…14,15 Whereas we preferred the use of the dual plating for the case, which can increase the fracture stabilization similar to the other 2-column fracture types like tibial plateau, distal humerus and plafond fractures. 16,17 In our case, surgery was done by 1 incision lateral to femur. Fibrotic areas and bone sequesters were debrided completely, obtained cancellous bone graft from iliac crest placed in the fracture site, direct reduction done followed by temporary fixation with K-wires, and longlocked lateral distal femoral plate used for the lateral column, then, under direct vision with neurovascular protection, a relatively small reconstructive plate was used at anteromedial distal femur for the medial column.…”
Section: Discussionmentioning
confidence: 92%
“…James et al evaluated the results of 24 geriatric patients treated with open reduction and conventional plating for a complex metaphysodiaphyseal fracture and reported successful results. 20 However, as open reduction and conventional plating was used in that study, the current study can be said to be the first to report the use of the MIPO method to treat metadiaphyseal fractures in geriatric patients. As mean life expectancy will increase in the future, this subject will be of greater importance.…”
Section: Discussionmentioning
confidence: 92%
“… 16 , 17 In the geriatric patient group in particular, impingement syndrome may sometimes severely restrict daily living activities. 20 Removal of the implant may be required in treatment. 22 Brunner et al reported that it was necessary to remove the implant in 3 patients of a series of 15.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 6 , 25 Moreover, ORIF does not address the common concomitant issues of glenohumeral arthritis and rotator cuff pathology, which can be found with geriatric proximal humerus fractures. 26 28 Utilizing magnetic resonance imaging analysis of proximal humerus fractures, rates of rotator cuff tears from 42% to 70% has been demonstrated, which can be associated with limited functional outcomes. 29 , 30 As a result, the current operative approach to complex proximal humerus fractures in this population has shifted largely towards RTSA utilization, with increasing literature support.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have advocated for fixation with complete open or minimally invasive locked plating. 26 28 ORIF of proximal humerus fractures in this patient population is associated with higher levels of technical difficulty, 26 outcomes that are operator dependent, 26 the possibility of subacromial impingement syndrome due to hardware prominence, 7 risk of axillary and radial nerve palsies, 28 and a two- to threefold increased risk of all complications when compared to younger patients. 40 Robinson et al presented the large series of patients treated with ORIF and found overall nonunion rate of 7%.…”
Section: Discussionmentioning
confidence: 99%